Estudo Fitoquímico das Folhas da Espécie Psychotria prunifolia (Kunth) Steyerm (Rubiaceae) - FARIA, Emiret Otoni de (2009)
Psychotria prunifolia is a Rubiaceae family specimen found in the Goiás cerrado , which is a huge ecosystem in the Brazilian Mid-West Mainland. The NCI (National Cancer Institute) highly referred to Psychotria as a hot genera with a cytotoxic potential from its extracts and fractions. Several related chemical studies have mostly indicated findings of indole alkaloid, which are keys to various biological activities. Current ongoing studies are focusing on phytochemical investigation of P. prunifolia, and its cytotoxic, antibacterial, antioxidant, and antifungal findings from its leaves extracts and fractions. It was feasible to isolate four new indole-monoterpene alkaloids and estrictosamida upon fractioning the leaves gross extracts. Estrictosamida has been found in and isolated from other specimens from the same genera. Recently-found alkaloids have been named prunifolina, prunifoliona, EPP26.2 e EPP28.1. Indole-monoterpene alkaloid is of greater chemotaxonomic importance for the Rubiaceae family, and it may assist with better classifying heteropsychotria sub-genera specimens. In vitro analysis of four cultures of cellular kinds, (S-180- Mice Sarcoma, A549- Human-Lung Carcinoma, K562 Chronic Human Myeloid Leukemia e HFF- 1-Regular Human Cells fibroblasts), has demonstrated successful cytotoxic activity of the P. prunifolia specimen. As a result of the antibacterial analysis, the leaves extracts were deemed to be less active. Extracts of leaves have shown little efficacy with its antioxidant potential, and in vitro antifungal analysis has indicated mild or little response.